Determination of Ghrelin Immunoreactivity in Kidney Tissues of Diabetic Rats - Kuloglu, Tuncay; Dabak, Durrin Ozlem (Taylor & Francis Ltd, 2009)
Backgrounds/Aims. Ghrelin, a recently discovered hormone, is released largely from stomach and might affect insulin secretion and glucose metabolism. The aim of this study was to determine the immunohistochemical localization of ghrelin in streptozotocin- induced diabetic rat kidneys. Methods. Fifty-four adult male Wistar rats were used in this study. All rats were divided into nine groups according to three time points of the study (2, 4, and 6 weeks) as control group, control group given 0.1 M phosphatecitrate, and diabetic group given 50 mg/kg streptozotocin intraperitoneally. The rats in all groups were decapitated at the end of 2, 4, and 6 weeks of the study. The kidneys of the rats were removed, and tissue samples were processed by using routine paraffin techniques. The samples were immunohistochemically stained using avidin-biotin-peroxidase method for ghrelin immunoreactivity. Results. There were no differences of ghrelin immunoreactivity between the control groups. Ghrelin immunoreactivity was observed in both distal tubulus and collecting ducts in the diabetic groups, while it was detected only in distal tubules of the control groups. The intensity of ghrelin immunoreactivity was increased at 4 and 6 weeks of the study in the diabetic groups. Conclusion. Increased ghrelin immunoreactivity in the diabetic rat kidney tissues suggests that ghrelin may contribute to the pathophysiological mechanism of diabetic nephropathy.
Keywords: diabetes mellitus; immunohistochemistry; kidney; ghrelin; rats